2017
DOI: 10.1186/s12955-017-0769-7
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children with congenital adrenal hyperplasia

Abstract: BackgroundChildren with congenital adrenal hyperplasia (CAH) require life-long glucocorticoid replacement and have daily intermittent hyper/hypocortisolemia and hyperandrogenemia. Health-related quality of life (HRQL) is important for understanding the impact the disease and therapy have on physical, mental, emotional, and social functioning. Little is known about HRQL in CAH. We compared HRQL in children with CAH to healthy norms and examined how these scores related to physiologic variables.MethodsA cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 23 publications
3
29
1
Order By: Relevance
“…Yau et al [ 66 ] found no differences in overall or specific health-related QoL between males and females, but again results were not presented separately. Halper et al [ 65 ] did not find any differences in QoL scores between sex and CAH subtypes. The results from these studies confirm that males with CAH may not have less psychological problems than females with CAH, highlighting the need for future research on this specific population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Yau et al [ 66 ] found no differences in overall or specific health-related QoL between males and females, but again results were not presented separately. Halper et al [ 65 ] did not find any differences in QoL scores between sex and CAH subtypes. The results from these studies confirm that males with CAH may not have less psychological problems than females with CAH, highlighting the need for future research on this specific population.…”
Section: Discussionmentioning
confidence: 95%
“…Five studies not included in this review, due to results not being presented separately across genders, also concluded with health-related Qol being affected in people living with CAH [ 65 69 ]. Halper et al [ 65 ] report no differences in scores between males and females, but findings were not presented separately, and this paper was therefore not included. The sample consisted of 45 children with CAH.…”
Section: Discussionmentioning
confidence: 99%
“…Other than in this study, all or the majority of patients with CAH included in QoL studies have had the classical phenotype. The reports are inconsistent and indicate varying degrees of impaired QoL (18,170,171,172,173,174). The outcome of genital surgery and satisfaction with sexual function affect the general wellbeing and are likely to affect the QoL of women with classic CAH, especially women with the null and I2 splice genotypes (175,176).…”
Section: Quality Of Lifementioning
confidence: 99%
“…The few studies investigating mental health issues in children with CAH show increased prevalence of ADHD, particularly for boys, and increased prevalence of anxiety disorders (155). Self rated QoL for children with CAH differ slightly from the proxyratings by their parents (156). The areas affected, as rated by the children, is fatigue, whereas their parents state academic underachievement, impaired physical and emotional health and psychosocial outcomes (157).…”
Section: Cahmentioning
confidence: 95%